Rainfall and Tidal Cycle Regulate Seasonal Inputs of Microplastic Pellets to Sandy Beaches - Balthazar-Silva, Danilo; Turra, Alexander; Moreira, Fabiana Tavares; Camargo, Rita Monteiro; Oliveira, Andrea Lima; Barbosa, Lucas; Gorman, Daniel (Frontiers in Environmental Science, 2020)
Microplastic contamination of coastal environments is a global problem and pellets used in industrial processes are a persistent form of microplastic pollution. Regions that host port facilities and industries may be sources of plastic pellets to local and adjacent coastal areas. This study assessed pellet densities over regional and local scales to provide a greater understanding of the spatio-temporal variation in its inputs to sandy beaches. Pellets were used as a proxy to undertake a multi-scale assessment of the spatial (local vs. regional) and temporal (tides and weather) stranding of microplastics. Regional variation was driven by weather (i.e., rainfall) and distance from source. Local-scale variability was driven by distance from source (along shore), tidal cycle, and beach hydrodynamics. Our results address the large spatio-temporal variability in microplastic pollution and provide useful information for monitoring programs by pointing to the need to consider variability in inputs over both regional and local scales.